Comparative evaluation of fibrin network formation after root conditioning using erbium, chromium-doped yttrium scandium gallium and garnet laser, ethylene-diamine-tetra-acetic acid, and tetracycline on dentin: A scanning electron microscopic study - Riya Liza Satish; Maya Rajan Peter; Anuradha Bhaskar; Rajesh Vylopillil; Biju Balakrishnan; Reshma Suresh (Wolters Kluwer Medknow Publications, 2023)
Context: Regeneration of periodontal tissues depend on the adhesion and development of fibrin clots to the root surface. Demineralization of the root surface ensures removal of smear layer uncovering dentin tubules and collagen matrix. Root conditioning agents were introduced to remove the smear layer and enhance the adhesion of blood components. Aims: The aim of the study was to determine the effect of erbium, chromium-doped yttrium, scandium, gallium and garnet (Er, Cr: YSGG) laser on smear layer removal (SLR) and fibrin network formation when compared to tetracycline, and ethylene-diamine-tetra-acetic acid (EDTA) for periodontal regeneration. Settings and Design: The study was conducted at Amrita school of dentistry and the study design involves in vitro comparative study. Subjects and Methods: Forty dentinal sections were prepared from freshly extracted teeth that were periodontally affected. The samples were divided into four groups: Scaling and root planing (SRP), tetracycline, EDTA, and Er, Cr: YSGG laser. The samples were assessed using a scanning electron microscope and photomicrographs were taken and analyzed for removal of smear layer, blood component adhesion (BCA), and fibrin network formation. Statistical Analysis Used: Analysis of variance test and Kruskal-Wallis test with P < 0.05 considered to be statistically significant. Results: There was a significant difference between Er, Cr: YSGG laser, tetracycline hydrochloride, and EDTA categories when compared with SRP categories. There was no significant difference between Er, Cr: YSGG laser, tetracycline, and EDTA according to SLR scoring and BCA scoring. Conclusions: It can be concluded that Er, Cr: YSGG laser-treated samples presented complete elimination of smear layer, formation of fibrin network, and BCA along with desensitizing effect for a better reduction in dentin hypersensitivity.